APPROACHES TO TEACHING SPECIAL SUBJECTS - Urinov Uygun Abdullayevich; Urakova Xabiba Baxtiyorovna (American Journals, 2023)
This article discusses approaches to teaching special subjects. Special subjects will be given detailed information about the use of methods in the classroom and the extent to which methods improve the effectiveness of the lesson.
Keywords: lesson, method, student, teacher, principle, education, skills, maxorart, information, qualifications, science.